Evaluation of DNA integrity of caprine cauda epididymal spermatozoa - Swain, Dilip Kumar; Swarnkar, Prasant; Kumar, Jitender; Yadav, Sarvajeet (The Indian Journal of Animal Sciences, 2012)
Sperm DNA integrity of the sperms recovered from cauda epididymis was evaluated by Comet assay to study the sperm DNA integrity and viability of the sperms through highly efficient fluorescent staining. With the advancement of the storage time, the viability and intactness of the sperm DNA got compromised. Our findings will strongly form a baseline data for further studies about the cauda epididymal sperms in terms of DNA integrity. We reported that cauda can be a source of retrieval of sperms for assisted reproduction after the death of the animal. We strongly argue for the development of suitable extenders with antioxidants for the reduction of free radical mediated damage to the sperms as well as optimal cryopreservation technique. The sooner the recovery of the sperms from the cauda the better the viability and an increased probability for fertilisation. Further studies are required to elucidate the key cellular and molecular mechanisms which are associated with the loss of quality of the epididymal sperms.